Food and nutrient intake of school-aged children in Lebanon and their adherence to dietary guidelines and recommendations - Lara Nasreddine; Nahla Hwalla; Fatima Al Zahraa Chokor; Farah Naja; Lynda O'Neill; Lamis Jomaa (BMC, 2022)
Abstract Background Lebanon, an Eastern Mediterranean country, is witnessing a remarkable nutrition transition, and the diets of school-aged children may be amongst those most affected. However, limited studies have examined the food consumption patterns and nutrient adequacy in this age group. Objectives The present study aimed to evaluate the dietary intakes of school-aged children in Lebanon and assess their adherence to nutrition guidelines and recommendations. Methods This study used data for 4-13 y-old children (n = 711) from a national cross-sectional survey conducted in 2014-2015 on a representative sample of Lebanese households with children. Dietary intake was assessed using single 24-h recall method. Estimated food group and nutrient intakes were compared to dietary recommendations and age-specific dietary reference intakes (DRI), including Estimated Average Requirements (EAR) and Acceptable Macronutrient Distribution Range (AMDR). Food group, energy, macro- and micro-nutrient intakes were presented for all children in the sample and stratified by age (4-8 y and 9-13 y) and sex. Results Mean energy intake of 4-13-year-old children was 1804 kcal/d. Almost half of the energy was provided by carbohydrates while 12% of children had protein intakes below EAR. Approximately three-quarters of children (4-13 y) exceeded the AMDR for total fat and saturated fats, and a similar proportion over consumed added sugars. The main sources of energy intake (EI) among children were the sweets, sweetened beverages and desserts followed by grains and mixed dishes. No significant differences were noted in %EI from different food groups, by sex, in either age groups. The highest adherence of children to food group recommendations was observed for the grains' food group (47.2-54.4%EI), while the lowest adherence was found for vegetables (3.1-14.1%EI). A high prevalence of vitamin and mineral inadequacies was noted amongst 4-13 y old children for key micronutrients, including vitamin D (99%), calcium (81%), and vitamin A (69.5%). Risk of inadequate micronutrient intakes was significantly increased among the older age group (p-value < 0.05). Conclusion Nutrient intakes of school-aged children in Lebanon reflect suboptimal nutrition. Educational and public health interventions are needed to promote healthier diets among children and prevent micronutrient deficiencies during this critical phase.